Strategi public relation bank syariah indonesia dalam meningkatkan pelayanan dan loyalitas nasabah di era digital - Andiani, Alycia Afina (Maliki Interdisciplinary Journal, 2025)
The digital transformation has reshaped communication and service patterns in financial institutions, including Bank Syariah Indonesia (BSI), which faces challenges in maintaining customer trust and loyalty amid rapid technological growth. This study addresses how BSI’s Public Relations (PR) strategies contribute to improving customer service and loyalty in the digital era. A descriptive qualitative approach was applied by reviewing relevant academic journals, including works by Dandy Affandy (2024), Mirzam Arqy Ahmadi (2024), Cici Insiyah (2025), and Novia Efriyanti (2024). The results indicate that PR plays a strategic role in building a positive image through transparent, educational, and Sharia-compliant digital communication. BSI’s PR strategies include social media engagement, corporate social responsibility (CSR) programs, and digital-based service enhancement to strengthen customer satisfaction and retention. The study concludes that the effectiveness of PR in the digital era is not solely determined by technological capability but also by the ability to uphold Sharia values and ethical communication in every public relations activity.